Preparation, Characterization, and Thermal Degradation Studies of p-Nitrophenol-Based Copolymer - Pawan P. Kalbende; Mangesh V. Tarase; Anil B. Zade (Journal of Chemistry)
Polycondensation reaction was employed to synthesize a new copolymer resin (p-NP-4,4′-MDA-F) from p-nitrophenol (p-NP) and 4,4′-methylene dianiline (4,4′-MDA) with formaldehyde (F) in presence of 2 M hydrochloric acid as a catalyst at 130±1°C. The resin was characterized by elemental analysis and spectral studies such as UV-visible, FT-IR, and 1H-NMR spectra which were used to confine the most probable structure of synthesized copolymer. Thermal degradation pattern and kinetics have been investigated by thermogravimetric analysis. Thermal degradation curve have been studied with minute detail for each degradation step. Friedman, Chang, Sharp-Wentworth, Freeman-Carroll, and Coat-Redfern methods have been implemented in order to compute the kinetic parameters, that is, thermal activation energy (Ea), order of reaction (n), and frequency factor (z).